2011
DOI: 10.2355/isijinternational.51.1852
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Precipitate in Vanadium-microalloyed Medium Carbon Steels Using Small-angle X-ray and Neutron Scattering Methods

Abstract: The microstructures and chemical composition of nano-precipitates in vanadium (V) steels were investigated by the alloy contrast variation method (ACV) using small-angle X-ray scattering (SAXS) coupled with small-angle neutron scattering (SANS) at holding temperatures ranging between 600 and 700°C. Both the SAXS and SANS profiles exhibited clear scattering, depending on the holding temperature, due to the presence of nano-precipitates. The scattering profiles of the precipitates are characteristic of spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
4
27
1
Order By: Relevance
“…If an external magnetic field is applied, the magnetic neutron scattering 127 is most pronounced perpendicular to the field and tends to zero in the parallel direction. 125 This can provide a way to remove the additional SANS arising from magnetic scattering, 128 but can also be used to select data arising from just the magnetic structure. To do this, measurements of the detected scattering in both positions are subtracted from one other to give the SANS from magnetic scattering alone.…”
Section: Precipitates and Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…If an external magnetic field is applied, the magnetic neutron scattering 127 is most pronounced perpendicular to the field and tends to zero in the parallel direction. 125 This can provide a way to remove the additional SANS arising from magnetic scattering, 128 but can also be used to select data arising from just the magnetic structure. To do this, measurements of the detected scattering in both positions are subtracted from one other to give the SANS from magnetic scattering alone.…”
Section: Precipitates and Clustersmentioning
confidence: 99%
“…This can be compared to the values calculated for expected precipitates. Systems studied using the ACV method include oxide clusters, 133 sulfide inclusions 134 and carbide precipitates 128 in a variety of different steels. This attractive method has advantages over TEM and even atom probe analysis, mainly in that it requires no sample perturbation, and could clearly be applied to other systems to gain insights into composition and crystallinity.…”
Section: Precipitates and Clustersmentioning
confidence: 99%
“…16) For the V added steels, Oba et al reported that nanoscale VC has off-stoichiometry in the early stage of precipitation. 15) Coakley et al reported partitioning of constituent elements to nanoscale ω precipitation in the titanium alloys. 17) As these examples show, the ACV technique is particularly useful when partitioning of the main constituent element occurs.…”
Section: Intermediate-angle Neutron Scattering Instrument For Quantitmentioning
confidence: 99%
“…[8][9][10] Odetta et al reported detailed microstructural analysis of oxide dispersed strengthened (ODS) steels using a combination of SANS, ATP and TEM. 11,12) SANS studies of nanoscale carbides such as TiC, 13) NbC 14) and VC 15) has been reported by different groups. In addition to these basic SAS applications, one of the authors (MO) proposed a new way to determine phase by the combining SANS and SAXS methods.…”
Section: Intermediate-angle Neutron Scattering Instrument For Quantitmentioning
confidence: 99%
“…3 using SANS and SAXS. [13][14][15][16][17] Most of them analyzed for nanoscale precipitates with a size of < 100 nm. Since SAS covers the analysis of quite a wide size range, from < 1 nm to > 1 μm, it is also useful for inclusions, which typically have sizes > 1 μm.…”
Section: Introductionmentioning
confidence: 99%